THE MAIN AREAS OF ACTIVITY OF THE CLASS LEADER IN THE EDUCATION OF THE NECESSARY SKILLS FOR AN INDEPENDENT LIFE IN STUDENTS - A. N. Ziyayev (Galaxy International Interdisciplinary Research Journal, 2022)
The article expresses the content of activities of the class leader in the management of the educational process on the education of the necessary skills for an independent life in students, as well as the problems and solutions that parents face in this regard.